2013
DOI: 10.1186/1756-3305-6-321
|View full text |Cite
|
Sign up to set email alerts
|

Study of the distribution and abundance of the eggs of Aedes aegypti and Aedes albopictus according to the habitat and meteorological variables, municipality of São Sebastião, São Paulo State, Brazil

Abstract: BackgroundThis study focused on the distribution and abundance of the eggs of Aedes aegypti and Aedes albopictus.MethodsEighty ovitraps were exposed for four days of each month in peri- and intradomiciliary environments of 40 urban residences on 20 street blocks that were drawn monthly in Sebastião, SP, between February 2011 and February 2012. The monthly distribution of positive ovitrap indices (POI) and mean egg counts per trap (MET) of Ae. aegypti and Ae. albopictus were analyzed using the Kruskal-Wallis te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 35 publications
6
32
1
6
Order By: Relevance
“…On top of that, the placement of the ovitraps can also indicate the neglected or the effectiveness of the current prevention and control measure such as larvicides application. Many researchers have reported in their studies, especially in Brazil and America, the ovitraps do not provide the estimation of Aedes mosquitoes population densities but they can give insight into relative changes in the adult female populations [16,30]. However, in this present study, the variables numbers of Aedes among study localities were observed in our data as tabulated in Table 3 and presented in Figure 2.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…On top of that, the placement of the ovitraps can also indicate the neglected or the effectiveness of the current prevention and control measure such as larvicides application. Many researchers have reported in their studies, especially in Brazil and America, the ovitraps do not provide the estimation of Aedes mosquitoes population densities but they can give insight into relative changes in the adult female populations [16,30]. However, in this present study, the variables numbers of Aedes among study localities were observed in our data as tabulated in Table 3 and presented in Figure 2.…”
Section: Discussioncontrasting
confidence: 54%
“…The utilization of ovitrap in this study may provide such information beneficial for planning and managing the dengue vectors. The ovitrap is proven to serve as the useful tools for providing the spatial and temporal data and successfully monitors the impacts of control measures [1,6,15,16]. Moreover, entomological studies in Taiwan reported that ovitrap data are more sensitive than the traditional way of larval survey in detecting the low population of Aedes mosquitoes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…(sand fly) and Ae. albopictus (Tsai et al, 2004;Chai et al, 2011;Serpa et al, 2013;Das et al, 2014). Several studies have been conducted to determine the average infected rate of Wolbachia in their respective hosts.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus and its association with number of residents and meteorological variables in the home environment of dengue endemic area [10]. Meanwhile, the meteorological factors [11] including area height, temperature, and rainfall were found in studies to be relevant to the DHF incidence [12], [13]. However, the DHF incidence in Samut Songkhram were not related to the meteorological factors because the province is small and drainage areas and natural water resources in Samut Songkhram were the Ae.…”
Section: Discussionmentioning
confidence: 99%